1999
DOI: 10.1063/1.123976
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and photoluminescence of alumina membranes with ordered pore arrays

Abstract: Porous alumina membranes with ordered pore arrays were prepared electrochemically from Al metal in C2H2O4 or H2SO4. Photoluminescence (PL) measurements show that a blue PL band occurs in the wavelength range of 400–600 nm. This band originates from singly ionized oxygen vacancies (F+ centers) in porous alumina membranes. Tentative reasons for the changes in intensity and peak position of the PL band with increasing heat-treatment temperature are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(188 citation statements)
references
References 9 publications
6
180
2
Order By: Relevance
“…The presence of oxygen vacancies has generally been considered to be responsible for the PL of anodic alumina (8, 9). Du et al (8) and Li et al (9) have attributed the blue emission band to singly ionized oxygen vacancies (F + centres) in AAMs formed in oxalic acid solution. In crystalline Al 2 O 3 , it has been shown experimentally that the F + centre can emit a PL peak at about 413 nm (3.0 eV) (16,17).…”
Section: Experimental Results and Analysesmentioning
confidence: 99%
“…The presence of oxygen vacancies has generally been considered to be responsible for the PL of anodic alumina (8, 9). Du et al (8) and Li et al (9) have attributed the blue emission band to singly ionized oxygen vacancies (F + centres) in AAMs formed in oxalic acid solution. In crystalline Al 2 O 3 , it has been shown experimentally that the F + centre can emit a PL peak at about 413 nm (3.0 eV) (16,17).…”
Section: Experimental Results and Analysesmentioning
confidence: 99%
“…Several methods have been used to confine or impregnate dyes in APA cavities [13]. Spectroscopic investigations are of use for in the confinement studies also of dye molecules [14][15][16][17]. The present work aimed to confirm that APA surface able to host macromolecules in to its pores.…”
Section: Fluorescence Intensity Measurementsmentioning
confidence: 51%
“…400 ∼ 600 nm range has been obtained with a maximum at about 450 nm. 15 Itou et al reported that PL emission bands centered at 330, 413 and 503 nm originate from F + (an oxygen vacancy occupied by one electron), F (an oxygen vacancy occupied by two electrons) and F 2 (an oxygen divacancy with four electrons) centers, respectively, in α-Al 2 O 3 nanostructures. 16 PL spectra from anodic alumina membranes exhibited two emission bands at around 405 and 455 nm, associated with F and F + centers, respectively.…”
Section: Resultsmentioning
confidence: 99%